Problematika Autentifikasi Hadis Periode Sahabat: Antara Keadilan dan Intrik Politik - Anam, Wahidul; Ilaina, Rudhad (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2023)
This paper attempts to uncover the problematic authentication of hadith traditions of the Companion period regarding the concept of "Companion justice. " It is a fundamental problem with granting authority in determining the quality of a hadith narrated by the women who were always detached from the political interests of the rulers of the time in which the women lived. This paper uses a literature study with a theological-normative approach and a historical approach. This study found that 1) The problems of authenticating the Hadith of the companions can be grouped into two, namely in terms of personality quality and faith and adherence to religious norms, and philosophical problems and scientific establishment. 2) The criticism Hadith of Abu Hurairah also shows a problematic existence in the authentication of Hadith during the era of the Companions. Therefore, Muslims should be cautious in following the traditions of certain Companions, who were already highly trusted to convey hadith traditions. This article implies the authority of the Companions in conveying Hadith. It needs to be reexamined, not merely that certain authorities tend takhlid, thus ignoring other narrators, who tend to be less favored by certain Islamic groups or influenced by certain political authorities.